A preliminary study of argumentation frameworks and argumentation schemes that appeal to expert opinion - Budán, Paola D. (2012)
The research in argumentation has produce systems with a human-like mechanism for commonsense reasoning. One form of repre- senting arguments is called Argumentation Schemes, in which are argu- ment forms that represent inferential structures of arguments used in everyday discourse, and in special contexts like legal argumentation, sci- enti c argumentation, and especially in AI. One type of argumentation scheme corresponds to appeal to Expert Opinion or Position-to-Know argumentation. Position-to-know reasoning is typically used in an infor- mation seeking type of dialogue where one has to depend on a source. Most of such argumentation frameworks are based on Dung's seminal work characterizing Abstract Argumentation Frameworks. In this work we introduce a novel framework, called Expert Argumentation Framework (EAF), extending AF with the capability of modeling the quality of expert associated with the arguments that proposed.